Application of information and communication technology in the Library of SMAN 1 Bandung - Alya Hafizza; Angga Hadiapurwa (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
The Library and Information Science Study Program of Universitas Pendidikan Indonesia has a vision to become a superior and characterful study program in the library and information science field. To achieve this vision, this study program organizes the Librarian Professionalism Internship Program as one of the mandatory programs for seventh-semester students. This program aims to provide students with direct experience in understanding librarianship practices, especially in school libraries. This program directly involves students practicing in the library and gaining experience in library management. The program results are then presented in writing using a qualitative approach and case study method with a focus on the application of ICT, organizing information, and user guidance. Through this program, students can learn various aspects of the implementation of librarianship, different from institutional libraries, and develop relevant technical (hard skills) and non-technical (soft skills). The school library itself has a strategic role as a means of supporting lifelong learning by providing easier access to information to students. The study results explain that the application of ICT in the SMAN 1 Bandung Library focuses more on the automation of library collections, while providing circulation services is still done manually.   Abstrak Program Studi Perpustakaan dan Sains Informasi Universitas Pendidikan Indonesia memiliki visi untuk menjadi program studi unggul dan berkarakter di bidang perpustakaan dan sains informasi. Sebagai bagian dari upaya pencapaian visi tersebut, program studi ini menyelenggarakan Librarian Professionalism Internship Program sebagai salah satu program wajib bagi mahasiswa semester tujuh. Program ini bertujuan untuk memberikan pengalaman langsung kepada mahasiswa dalam memahami praktik kepustakawanan, khususnya di perpustakaan sekolah. Program ini langsung melibatkan mahasiswa untuk langsung praktik di perpustakaan dan menggali pengalaman dalam pengelolaan perpustakaan. Hasil dari program tersebut kemudian disampaikan secara tertulis dengan menggunakan pendekatan kualitatif dan metode studi kasus dengan berfokus pada penerapan TIK, pengorganisasian informasi, dan bimbingan pemustaka. Melalui program ini, mahasiswa dapat mempelajari berbagai aspek pelaksanaan kepustakawanan yang berbeda dari perpustakaan lembaga, serta mengembangkan kemampuan teknis (hard skills) dan non-teknis (soft skills) yang relevan. Perpustakaan sekolah sendiri memiliki peran strategis sebagai sarana pendukung pembelajaran sepanjang hayat dengan memberikan akses informasi yang lebih mudah kepada peserta didik. Hasil dari penelitian menjelaskan bahwa penerapan TIK di Perpustakaan SMAN 1 Bandung lebih berfokus pada otomasi koleksi perpustakaan sedangkan dalam menyajikan layanan sirkulasi masih dilakukan secara manual. Kata Kunci: magang; manajemen perpustakaan; perpustakaan sekolah